2012
DOI: 10.1016/j.jmbbm.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of cardiac growth: In vivo characterization of growth tensors and strains

Abstract: Progressive growth and remodeling of the left ventricle are part of the natural history of chronic heart failure and strong clinical indicators for survival. Accompanied by changes in cardiac form and function, they manifest themselves in alterations of cardiac strains, fiber stretches, and muscle volume. Recent attempts to shed light on the mechanistic origin of heart failure utilize continuum theories of growth to predict the maladaptation of the heart in response to pressure or volume overload. However, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 53 publications
5
24
0
Order By: Relevance
“…In a recent long-term study in infarcted sheep, we have found a significant chronic fiber lengthening, accompanied by a chronic radial shortening [51], which agrees nicely with the format of our growth tensor in equation (3). In freshly isolated cardiac tissue, compared with a healthy control group, cardiomycytes from patients with dilated cardiomyopathy were reported to be 40% longer, while the cell widths displayed no statistically significant differences [11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a recent long-term study in infarcted sheep, we have found a significant chronic fiber lengthening, accompanied by a chronic radial shortening [51], which agrees nicely with the format of our growth tensor in equation (3). In freshly isolated cardiac tissue, compared with a healthy control group, cardiomycytes from patients with dilated cardiomyopathy were reported to be 40% longer, while the cell widths displayed no statistically significant differences [11].…”
Section: Discussionsupporting
confidence: 87%
“…Motivated by physiological observations, we introduce a single scalar-valued growth multiplier ϑ , which reflects the longitudinal growth of individual heart muscle cells through serial sarcomere deposition [12]. We assume that cardiac dilation is an isochoric process characterized through growth along the fiber direction f 0 and simultaneous shrinkage orthogonal to f 0 such that the overall tissue volume remains constant [51]. …”
Section: Continuum Modeling Of Cardiac Growthmentioning
confidence: 99%
“…For example, some groups have used high-speed X-ray of implanted metal markers-a decades-old technique for measuring beat-to-beat tissue mechanics in the heart-to quantify transmural gradients in tissue remodeling following myocardial infarction or imposition of hemodynamic overload in animals [20][21][22]. Because it can provide real-time, coupled data on regional mechanics and G&R at multiple locations and time points, this approach could be very valuable in validating and calibrating growth models.…”
Section: Growth and Remodeling Models Come Of Agementioning
confidence: 99%
“…Compared to continuum models, multi-scale models and cellular level frameworks can more practically simulate cell-cell communication, cell differentiation, cell migration, and signaling pathways that govern vascular growth (Egginton 2011; Guidolin et al 2009; Travasso et al 2011). Detailed three-dimensional growth kinematic analysis has also been employed in finite-element models as well as in the quantitative analysis of in vivo growth (Goktepe et al 2010; Tsamis et al 2012). However, none of these models has yet attempted to integrate multiple scales, organ- and cell-level functional requirements, and three-dimensional tissue level structural growth organization.…”
Section: Predictive Computational Engineering Studiesmentioning
confidence: 99%